Innovative Approach to Women's Economic Empowerment Through MSMEs: A Case Study of Preneurlamongan Megilan in Maduran District - Ahmad Munir Hamid (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze women's economic empowerment strategies through a community-based MSME program known as Thug (Preneur Lamongan Megilan) in Maduran District, Lamongan. This program is designed to improve women's skills, competitiveness, and economic independence through micro, small, and medium enterprises (MSMEs). This research will highlight the role of women in the local economy, the challenges faced, and the socio-economic impact of this empowerment on the well-being of families and communities. This study uses a qualitative method with a case study approach to explore the dynamics in the field. The results of this study are expected to provide deeper insight into women's contribution to local economic development and provide appropriate policy recommendations to support women's economic empowerment in Lamongan. Thus, it is hoped that the Thug program can continue to develop and provide real benefits for the local community. The success of this program is also expected to be an inspiring example for other regions in an effort to improve community welfare through community-based MSMEs.